OP0224-HPR Identifying Clinically Significant Fatigue in Rheumatic Diseases: A Case-Definition Approach. (9th June 2015) - Kwakkenbos, L.; Minton, O.; Stone, P.; Alexander, S.; Baron, M.; Hudson, M.; Thombs, B.
Abstract : Background: Fatigue is common across rheumatic diseases and is a crucial determinant of quality of life. Most studies use single questions or scores above a cut-off point on a continuous measurement scale to define fatigue. These methods, however, are not benchmarked to a case-definition standard and do not necessarily identify clinically significant fatigue levels that warrant investigation and treatment. The lack of agreed-upon standards for identifying clinically significant fatigue hinders research and clinical management. Case definition criteria for Cancer-Related Fatigue were proposed for inclusion in ICD, but to apply the criteria more broadly to define Chronic Illness-Related Fatigue, criteria items must be measurement equivalent across disease groups, meaning that patients across disease groups with similar levels of fatigue will respond similarly to items. Objectives: The objective was to evaluate whether the Cancer-Related Fatigue case definition performs equivalently in women with breast cancer and systemic sclerosis (SSc) and could be used to identify patients with Chronic-Illness Related Fatigue. Methods: The Cancer-Related Fatigue interview was completed by 291 women with SSc and 278 women successfully treated for breast cancer. The diagnostic interview determined whether patients met the following criteria; the presence of 2 weeks of significant fatigue in the preceding month and the presence of at least five out of nine other fatigue-related symptoms. In addition, there is a single item that assesses whether fatigue has a significant effect on work or self care. Finally, the symptoms cannot be primarily a consequence of a co-morbid psychiatric disorder, primarily depression. Differential item functioning was assessed with the Multiple-Indicator Multiple-Cause model (MIMIC). Results: The mean age in the SSc sample was 58.1 years (SD=11.5) and mean time since diagnosis was 10.5 years (SD=8.5). Most patients (n=219, 75.5%) were diagnosed with limited SSc (n=211, 72.8%). In the cancer sample, the mean age was 57.9 years (SD=11.4) and the mean time post-treatment was 11.1 months (SD=6.6). Results of the MIMIC analyses showed that items 3 (concentration) and 10 (short-term memory) were endorsed significantly less often by women with SSc compared to cancer, controlling for responses on other items. Omitting these 2 items from the case definition and requiring 4 out of the 7 remaining symptoms resulted in a similar overall prevalence of Cancer-Related Fatigue in the cancer sample compared to original criteria (37.4% versus 37.8%, respectively) with 97.5% of patients diagnosed identically with both definitions. Prevalence of Chronic Illness-Related Fatigue was 36.1% in SSc using 4 of 7 symptoms. Conclusions: The Cancer-Related Fatigue criteria can be used equivalently to identify patients with Chronic Illness-Related Fatigue when two cognitive fatigue symptoms are omitted. Harmonized definitions and measurement of clinically significant fatigue will advance research and clinical management of fatigue in rheumatic diseases and other conditions. For instance, targeting fatigue interventions to patients with clinically significant fatigue, using the proposed case-definition, would increase the potential for improvement. Disclosure of Interest: None declared